Clinical Toxoplasmosis in Dogs and Cats: An Update - Calero-Bernal, Rafael; Gennari, Solange M. (Frontiers in Veterinary Science, 2019)
Toxoplasmosis is caused by the globally distributed protozoan parasite Toxoplasma gondii (phylum Apicomplexa); the disease can be clinically important for almost all homeothermic animals, including birds and humans. Toxoplasmosis course involves general clinical signs, such as fever, anorexia, or dyspnea, and more specific signs with neural, respiratory, cutaneous, or ocular involvement. Because of the wide range of clinical signs, the diagnosis in domestic and pet animals can be complicated. Hence, this review aims to provide a comprehensive analysis of some scarcely discussed aspects of toxoplasmosis, such as ocular and cutaneous manifestations, congenital infections, influence of T. gondii genotype on clinical toxoplasmosis, and recent findings regarding differential diagnosis. This review could be of special interest to clinicians and researchers.